Historical sketch book and guide to New Orleans and environs, with map... - Hearn | Lafcadio... (Wikimedia Commons, 1885)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: Histoire; iconographie; gravure; photographie; Wikimedia Commons; Iconographie